The nth term of an arithmetic sequence is given by `a_n=a_1+(n-1)d` where `a_1` is the first term of the sequence, and `d` is the common difference between two successive terms.

Given the sequence -7,-1,5,11,... we see that the common difference is6 (We add 6 to each term to get the next term), so d=6 and `a_1=-7`

So `a_10=-7+(10-1)(6)=-7+54=47`

------------------------------------------------------------------

**The tenth term of the sequence is 47**

------------------------------------------------------------------

-7,-1,5,11,17,23,29,35,41,**47**,...

Note that the terms of the sequence lie on a line; the common difference is the slope. Since the slope is 6 and we have the "point" (1,-7) we can find the equation of the line: `y-(-7)=6(x-1)` or `y=6x-13` . Then when x=10 we have y=60-13=47.

in the series -7, -1, 5,11, ... we can see tat the difference between 2 no's is 6. so thereby if we add 6 to each no ie. -7,-1,5,11,17,23,29,35,41,**47. **

**thus answer is 47**